2001
DOI: 10.1053/euje.2001.0092
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostics of Main Coronary Artery Stenoses and Occlusions: Multiplane Transoesophageal Doppler Echocardiographic Assessment

Abstract: Transoesophageal Doppler evaluation of coronary blood flow with application of a modified continuity equation is an accurate, non-invasive method of coronary arteries stenoses diagnostics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 13 publications
1
17
0
Order By: Relevance
“…5 In a comparative study of 94 patients, a high correlation was found between the results of TEE and quantitative coronary angiography for the LMCA, LAD, LCx and RCA. 6 Also, a good linear correlation was found between TEE derived luminal percent area stenosis, using a modified continuity equation, and quantitative angiography. 6 In addition, three dimensional transesophageal echocardiography was found to be successful in delineating normal and stenotic proximal coronary arteries.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…5 In a comparative study of 94 patients, a high correlation was found between the results of TEE and quantitative coronary angiography for the LMCA, LAD, LCx and RCA. 6 Also, a good linear correlation was found between TEE derived luminal percent area stenosis, using a modified continuity equation, and quantitative angiography. 6 In addition, three dimensional transesophageal echocardiography was found to be successful in delineating normal and stenotic proximal coronary arteries.…”
Section: Discussionmentioning
confidence: 97%
“…6 Also, a good linear correlation was found between TEE derived luminal percent area stenosis, using a modified continuity equation, and quantitative angiography. 6 In addition, three dimensional transesophageal echocardiography was found to be successful in delineating normal and stenotic proximal coronary arteries. 7,8 The LMCA, LAD, LCx and RCA were visualized in 100%, 100%, 98%, and 72% of the patients, respectively, with a sensitivity and specificity in detecting significant stenosis of 84% and 97%.…”
Section: Discussionmentioning
confidence: 97%
“…The optimal techniques are IVUS and FFR measurements, however these techniques are extremely expensive, not widely available, and require special training. Non-invasive techniques like TEE or TTDE using a high frequency transducer are useful for noninvasive evaluation of flow velocity dynamics in the LM [12,20-22,32]. Doppler-TTE is a simple, widely-used, and noninvasive procedure that does not require lengthy preparation and post-examination observation, therefore can be used for routine screening of patients with known ambiguous LM as adjunct to other invasive or non-invasive diagnostic modalities.…”
Section: Discussionmentioning
confidence: 99%
“…Transesophageal Doppler evaluation of coronary blood flow may help to detect the coronary arteries stenoses. 4 The left main coronary artery peak diastolic flow velocity of 1.4 m/s can be considered a criteria for hemodynamically significant coronary stenosis. Another Doppler criterion 5 suggesting the presence of a significant coronary stenosis is a ratio of Ն2.0 for maximal blood flow velocity at the site of the stenosis to the prestenotic flow velocity.…”
mentioning
confidence: 99%